ROOTING OF NANDINA CUTTINGS USING DIFFERENT SUBSTRATES - CARVALHO, Ruy Inacio Neiva de; GOSEK, Carlos Fernando (Scientia Agraria, 2008)
Nandina domestica is an exotic ornamental plant which is easily propagated by seeds. In the future, due to creation of new sterile cultivars, its commercial propagation is prone to be strictly asexual. The objective of this work was to evaluate the rooting ability of semi-hardwood nandina cuttings in different substrates. Semi-hardwood cuttings were collected from a parent plant located in São José dos Pinhais, PR. Cuttings without leaves, made 15 cm long, were kept in greenhouse under intermittent mist. Sand, soil, vermicompost and vermiculite substrates were evaluated. A randomized complete block design with five replications of the four treatments, using 10 cuttings per experimental unit, was used. The rooting percentage, the number of cuttings presenting callus, with shoots but no roots and dead cuttings and the dry mass of roots and shoots were evaluated. Sand allowed 70% rooting and the production of 0.373 g of roots and 13.45 g of shoots per cutting. There was no callus formation in any of the tested substrates. A high mortality percentage (54%) of cuttings was observed in the vermiculite substrate. Sand was the most suitable substrate for rooting of nandina cuttings, which was accompanied by an elevated root and shoot dry mass production.